Anxiety Levels of Fencing Athletes in Kudus Regency In Facing the 2026 Central Java Provincial Sports Week (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the level of anxiety experienced by fencing athletes from Kudus Regency in facing the 2026 Central Java Provincial Sports Week (PORPROV). This study uses a descriptive quantitative approach with a sample of 24 athletes selected through a purposive sampling technique. Data collection was carried out through the distribution of the Sport Anxiety Scale (SAS) questionnaire, which has been tested for validity and reliability. Prerequisite tests include a normality test using the Kolmogorov–Smirnov method, which produces a significance value of 0.200 and a homogeneity test using Levene's Test with a significance value of 0.696, indicating that the data are normally distributed and homogeneous. Data analysis was carried out using descriptive statistical techniques and the One-Way ANOVA test. The results of the study showed that the anxiety level of fencing athletes was generally in the "Somewhat Low" category, with an average value of 38.96, the lowest score being 26 and the highest being 57 out of a maximum score of 88. The ANOVA test showed a significance value of 0.093, which indicated there was no significant difference in anxiety between the Cadet, Junior, and Senior athlete categories. These findings revealed that most athletes could manage psychological stress fairly stably. This study provides implications for coaches and sports trainers to integrate mental training into athlete development programs.